2011
DOI: 10.1007/s00423-011-0779-6
|View full text |Cite
|
Sign up to set email alerts
|

A new pouch reconstruction method after total gastrectomy (pouch-double tract method) improved the postoperative quality of life of patients with gastric cancer

Abstract: PDT is safe and associated with better nutritional status compared with the RY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…The interposition of the jejunum between the esophagus and duodenum provides advantages in terms of nutritional benefits by secreting hormones through the duodenal passage and endoscopic accessibility to the duodenum, biliary tract, and pancreas. Recently, postoperative advantages of DT after TG have been reported, in terms of patients' BW, quality of life, and nutritional conditions [14]. Takase et al [10] concluded that fat absorption influenced nutrition in BW recovery of patients after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interposition of the jejunum between the esophagus and duodenum provides advantages in terms of nutritional benefits by secreting hormones through the duodenal passage and endoscopic accessibility to the duodenum, biliary tract, and pancreas. Recently, postoperative advantages of DT after TG have been reported, in terms of patients' BW, quality of life, and nutritional conditions [14]. Takase et al [10] concluded that fat absorption influenced nutrition in BW recovery of patients after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Another research found that BW gain was better in the group with preserved duodenal passage compared to the group without it in periods of 12 and 24 months after the operation [2]. Also, patients treated by TG and esophagojejunostomy with RY occasionally have dysphagia and appetite loss that result in BW loss [14]. Kalmár et al [15] reported that TG leads to significant BW loss in 40-90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many patients and surgeons have become interested in quality of life after surgery because the 5 year survival rate for early gastric cancer has been reported to be as high as 90%. [4][5][6] Minimally invasive surgery for early gastric cancer, including endoscopic submucosal dissection, laparoscopic gastrectomy, and robotic gastrectomy, can improve the patient's quality of life after surgery. Among the minimally invasive surgical techniques, great advances have been made in the surgical treatment of early gastric cancer with laparoscopic gastrectomy.…”
mentioning
confidence: 99%
“…Early gastric cancer (EGC) is defined as adenocarcinoma in which the depth of invasion is confined to the mucosa or submucosa, irrespective of lymph node metastasis, and has a good prognosis with surgical curative resection [5]. Many surgeons are very interested in the patient's quality of life, because most patients can be cured after surgery [6,7,8]. Many clinical studies have been carried out on long-term survival results and short-term postoperative outcome in order to clarify the advantages of laparoscopy-assisted distal subtotal gastrectomy (LADG) for EGC patients [9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%